Pengaruh Circuit Training Terhadap Kelincahan, Daya Ledak Otot Tungkai, dan Daya Ledak Otot Lengan Atlet Bolabasket MAN Kota Surabaya - Ilma Suryana; Himawan Wismanadi; Mokh. Nur Bawono; Roy Januardi Irawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of circuit training on agility, leg muscle explosive power, and arm muscle explosive power of basketball athletes at MAN Kota Surabaya. This study employed a quasi-experimental method with a one-group pre-test and post-test design. The subjects consisted of 15 basketball athletes participating in extracurricular activities. The instruments used were the Illinois Agility Test to measure agility, Jump MD for leg muscle explosive power, and Medicine Ball Throw for arm muscle explosive power. The circuit training program was conducted for eight weeks with a frequency of three sessions per week. Data were analyzed using a paired sample t-test. The results showed significant improvements in all variables, with significance values for agility (p = 0.000), leg muscle explosive power (p = 0.000), and arm muscle explosive power (p = 0.000). In conclusion, circuit training has a significant effect on improving agility as well as leg and arm muscle explosive power of basketball athletes at MAN Kota Surabaya. Keywords: basketball, circuit training, muscle explosive power, agility